2001
DOI: 10.3758/bf03194520
|View full text |Cite
|
Sign up to set email alerts
|

The effects of abrupt onset of 2-D and 3-D distractors on prehension movements

Abstract: This article includes two experiments aimed at investigating how two-dimensional (2-D) and threedimensional (3-D) distractors affect the kinematics of prehension and aiming movements in order to understand the attentional processes involved in visuomotor control. In Experiment 1, subjects grasped large targets in the presence of both large and small 3-D distractors and their corresponding 2-D photographs. The distractors appeared for either 10 sec or appeared simultaneously with the target presentation. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…In line with this idea, Holmes and Heath (2013) reported that although the size of real objects and images could be estimated equally well, observers used different grip strategies during grasping of real objects and images. Analogous findings were also reported by Castiello (1998Castiello ( , 2001 who found that real 'distractor' objects (but not photographs of the same items) interfered with the kinematics of reaching and grasping responses. Snow et al (2011) found different neuroimaging effects of repetitions for real objects versus matched photographs of the same items, suggesting that the human brain may process and/or represent real graspable objects differently from pictures.…”
Section: Introductionsupporting
confidence: 77%
“…In line with this idea, Holmes and Heath (2013) reported that although the size of real objects and images could be estimated equally well, observers used different grip strategies during grasping of real objects and images. Analogous findings were also reported by Castiello (1998Castiello ( , 2001 who found that real 'distractor' objects (but not photographs of the same items) interfered with the kinematics of reaching and grasping responses. Snow et al (2011) found different neuroimaging effects of repetitions for real objects versus matched photographs of the same items, suggesting that the human brain may process and/or represent real graspable objects differently from pictures.…”
Section: Introductionsupporting
confidence: 77%
“…Consistent with previous reports, arm trajectories changed their shape when targets of different size were used, and this effect was chiefly due to modifications in the deceleration phase (MacKenzie et al ., ; Gentilucci et al ., ; Castiello, ). Fitt's law (1954) was found to apply, given that movement time increased as a function of task difficulty.…”
Section: Discussionmentioning
confidence: 98%
“…This is a puzzling result given that evidence in humans indicates that the kinematical organization of reaching is affected by the precision requirements related to intrinsic features of objects such as size (MacKenzie et al, 1987; Gentilucci et al, 1991; Castiello, 2001). In this perspective we would have expected increased AIP activity as a reflection of the need for more on-line control required by reaching small objects.…”
Section: Discussionmentioning
confidence: 99%